The degree of practicing Islamic administrative thought among Arab school principals in AL- Naqab region from the teachers’ point of view - Okbi, Sabri Naif; Al-Hiyari, Hassan Ahmed; Eabidat, Hani Hatmal (Linguistics and Culture Review, 2021)
The study aimed to identify the degree of Islamic administrative thought practice among Arab school principals in the Negev region from the teachers’ point of view. Male and female teachers and the study sample consisted of male and female teachers who were chosen by the available random method at a rate of (5%). The results revealed that there were no statistically significant differences in the degree of practicing Islamic administrative thought among Arab school principals in the Negev region due to the variable (gender, practical qualification), and the presence of statistically significant differences in the variable (experience), which came in favor of (10 years or less). In light of the results of the study, the researcher recommends that the principle of Arab schools in the Negev region should continue to practice Islamic administrative methods because of their positive effects on work.